Do firms provide wage insurance against shocks? Evidence from Hungary - Gábor Kátay (European Central Bank (ECB), 2008)
In this paper I address the question to what extent wages are affected by product market uncertainty. Implicit contract models imply that it is Pareto optimal for risk neutral firms to provide insurance to risk averse workers against shocks. Using matched employer-employee dataset, I adopted the estimation strategy proposed by Guiso et al. (2005) to evaluate wage responses to both permanent and transitory shocks in Hungary and compared my results to similar studies on Italian and Portuguese datasets. I found that firms do insure workers against product market uncertainties, but the magnitude of the wage response differs depending on the nature of the shock. Broadly speaking, the wage response to permanent shocks is twice as high as the response to transitory shocks. Comparing my results to the two other studies, the main dierence lies in the elasticity of wages to transitory shocks. Unlike these previous findings, my results show that full insurance to transitory shocks is rejected.
Keywords: C33; D21; J33; J41; 330; matched employer-employee data; optimal wage contract; product market uncertainty; Risk Sharing; wage insurance; Arbeitskräfte; Lohn; Lohnrigidität; Arbeitsvertrag; Schock; Schätzung; Ungarn